HUKUM ADAT DALAM PUTUSAN PENGADILAN (ADAT LAW IN COURT'S DECISIONS) - Setiawati, Wenny (UI Scholars Hub, 2013)
This little book is proven to be not so lightweight after the reading. At first, the number of page which is only 74 pages gave the feeling of light reading material, but the opposite result took place. Since this book was filled with court decisions on the various cases related to customary legal system, so the reader would need all of his focus in understanding the hidden lines within the reading.